2017
DOI: 10.5430/jnep.v8n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implementing an educational module on improving mothers knowledge, home management and attitude about febrile convulsion

Abstract: Background/Objective: Febrile convulsions (FCs) are the most common convulsive disorder of childhood, and represent a benign condition in children. FC occurrence can affect negatively on the familial quality of life and the parents may experience anxiety and fear with every time child develops fever. Therefore, parents and care givers should be educated about febrile convulsion and its home management. The aim of this study was to evaluate the effect of implementing an educational module on mother's knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
(24 reference statements)
5
15
0
Order By: Relevance
“…This finding disagreed with Elbilgahy and Abd El Aziz [19], in their Egyptian research as they reported that there were a relation between their studied mothers' total knowledge scores and their total practices and attitudes scores but the relation was not statistically significant.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…This finding disagreed with Elbilgahy and Abd El Aziz [19], in their Egyptian research as they reported that there were a relation between their studied mothers' total knowledge scores and their total practices and attitudes scores but the relation was not statistically significant.…”
mentioning
confidence: 58%
“…Similarly [19], mentioned in their Egyptian study at Mansoura University Children's Hospital that the implementation of educational sessions and also mothers support group were influenced positively in enhancing mothers' knowledge. Similarly to these present findings [1], concluded in their study in India that educational program about treatment of children suffering from pyrexia was effective in increasing the level of knowledge of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Also in an agreement with Barzegar et al (2016) (15) who stated that the handout assembles and the (12) in Iraq who found that 55% of parents believe that if it is necessary a lumbar puncture can be done. an Egyptian study (6) showed that one quarter Conversely, a study done in Libya (8) (14) in Iran who reported that less than one-quarter of the mothers took their children to the hospital or clinic without first aids at the time of FC. Also a study was done in Iraq (12) found that only The current study showed that 43.8% Pry the convulsing child's clenched teeth apart and put something in his/her mouth.…”
Section: Discussionmentioning
confidence: 99%
“…recommended management and first aid of febrile convulsions). (6) The questionnaire took about 20 minutes to be filled in each time; patient education session took about 30 minutes and applied either individually or in small groups, 3 main prescheduled health education sessions were implemented in the health center targeting attended mothers not included in the study.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Usually, childcare providers are the first responders to emergencies, including FCs, at childcare centers, although they do not appear to cope well with emergencies [ 10 ]. They may hurriedly take children with FCs to emergency rooms without preventing aspiration and keeping the children’s airway clear as the most crucial first-aid treatment for FCs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%